2011
DOI: 10.1002/mus.22067
|View full text |Cite
|
Sign up to set email alerts
|

Median nerve changes following steroid injection for carpal tunnel syndrome

Abstract: Introduction Neuromuscular ultrasound is a painless, radiation-free, and high-resolution imaging modality for assessment of the peripheral nervous system. The purpose of this study was to use neuromuscular ultrasound to assess the changes that occur in the median nerve following steroid injection for carpal tunnel syndrome (CTS). Methods Ultrasound and nerve conduction studies were performed at baseline and 1 week, 1 month, and 6 months after steroid injection in 19 individuals (29 wrists) with CTS. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
67
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(75 citation statements)
references
References 16 publications
5
67
1
2
Order By: Relevance
“…The results of the study by Cartwright et al 2 are in line with the literature in showing that symptom improvement occurs within 1 week from injection. [5][6][7][8][9] This early symptomatic, objective, and electrophysiological improvement persisted for up to 6 months in most patients.…”
supporting
confidence: 84%
See 1 more Smart Citation
“…The results of the study by Cartwright et al 2 are in line with the literature in showing that symptom improvement occurs within 1 week from injection. [5][6][7][8][9] This early symptomatic, objective, and electrophysiological improvement persisted for up to 6 months in most patients.…”
supporting
confidence: 84%
“…Very few studies have been done after surgery, and none have been reported after local steroid therapy until the study by Cartwright and colleagues. 2 As often happens in the medical field, when a new tool is introduced, its role in following treatment-related changes is studied only in a subsequent phase. The time has probably come to consider US not only for its role in depicting nerves but also to monitor the response (or the failure to respond) of diseases to therapy as well as to assess the natural course of diseases.…”
mentioning
confidence: 99%
“…Excess blood flow would tend to engorge the nerve and, because blood is much less echoic than tissue, would reduce nerve echogenicity. 7073 Both ultrasound-guided steroid injections and surgical treatment of carpal tunnel syndrome lead to prompt and sustained reductions in nerve size as measured by cross-sectional area. 7072,74,75 When Cartwright and colleagues 70 looked at median nerve vascularity in conjunction with nerve size, both decreased in tandem in patients with carpal tunnel syndrome after ultrasound-guided steroid injections around the median nerve.…”
Section: Quantification Of Nerve Ultrasonographymentioning
confidence: 99%
“…Buchberger et al demonstrated the enlargement and deformation of the median nerve with ultrasonography for the first time and described the characteristic features that could be found in patients with CTS [24]. Cartwright et al reported significant changes in median nerve CSA after steroid injection, and the nerve CSA correlated with symptom score and electrodiagnostic parameters [2]. Meys et al reported that patients who did not need surgery within the 1 year after steroid injection had a lower median nerve ultrasonographic CSA, a lower swelling ratio, and a lower symptom severity score [3].…”
Section: Discussionmentioning
confidence: 96%
“…The ultrasonographic changes that occur within the median nerve of those undergoing steroid injection for CTS have recently been reported [2]. The most consistent finding in MSUS for CTS is a significant increase in the cross-sectional area (CSA) of the nerve at the pisiform bone level (equivalent to the carpal tunnel inlet) [3].…”
Section: Introductionmentioning
confidence: 96%